Colombia Gender Assessment - World Bank Group (World Bank, Washington, DC, 2019)
Achieving gender equality in Colombia is critical to the country’s future economic development and social cohesion; yet it remains an ongoing challenge. The government of Colombia recognizes the importance of closing the country’s gender gaps and is working on multiple fronts to realize this objective. However, and although preliminary findings indicate that substantial progress has been made over the last two decades, several challenges remain. Using the framework provided by the 2012 World Development Report, this assessment allows identifying the main existing gender gaps across the areas of agency, endowments and economic opportunity, and the major driving factors with regards to households, institutions and markets (chapters one, two, three, and four). Based on this diagnostic, chapter five provides some policy recommendations that may help to close the existing gender gaps.